Medicinal Purposes: Bioactive Metabolites from Marine-derived Organisms - Li, Tingting; Ding, Ting; Li, Jianrong (Mini Reviews in Medicinal Chemistry, 2019)
The environment of marine occupies about 95% biosphere of the world and it can be a critical source of bioactive compounds for humans to be explored. Special environment such as high salt, high pressure, low temperature, low nutrition and no light, etc. has made the production of bioactive substances different from terrestrial organisms. Natural ingredients secreted by marine-derived bacteria, fungi, actinomycetes, Cyanobacteria and other organisms have been separated as active pharmacophore. A number of evidences have demonstrated that bioactive ingredients isolated from marine organisms can be other means to discover novel medicines, since enormous natural compounds from marine environment were specified to be anticancer, antibacterial, antifungal, antitumor, cytotoxic, cytostatic, anti-inflammatory, antiviral agents, etc. Although considerable progress is being made within the field of chemical synthesis and engineering biosynthesis of bioactive compounds, marine environment still remains the richest and the most diverse sources for new drugs. This paper reviewed the natural compounds discovered recently from metabolites of marine organisms, which possess distinct chemical structures that may form the basis for the synthesis of new drugs to combat resistant pathogens of human life. With developing sciences and technologies, marine-derived bioactive compounds are still being found, showing the hope of solving the problems of human survival and sustainable development of resources and environment.
Keywords: Antibacterial